INTEGRATING HRIS AND DIGITAL TECHNOLOGIES FOR SUSTAINABLE AND ADAPTIVE HUMAN RESOURCE STRATEGIES - Oktarianti, Via; Veri, Jhon (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: In the era of accelerated digital transformation, organizations must adopt technology-driven solutions to manage human resources effectively. This study aims to examine the integration of Human Resource Information Systems (HRIS) with digital technologies such as HR Analytics and Artificial Intelligence (AI) in developing sustainable and adaptive human resource strategies. Using a qualitative descriptive approach supported by recent empirical studies, this research analyzes how data-driven insights and automation improve decision-making, operational efficiency, and workforce adaptability. The findings reveal that integrating HRIS with digital tools enhances organizational agility by optimizing talent management processes, promoting sustainability, and aligning human capital initiatives with strategic goals. The study concludes that digital integration in HR functions not only improves performance and efficiency but also strengthens long-term organizational resilience in a dynamic business environment..Keyword: HRIS; HR Analytics; Artificial Intelligence; Sustainability; Organizational AgilityAbstrak: Di era transformasi digital yang semakin cepat, organisasi harus mengadopsi solusi berbasis teknologi untuk mengelola sumber daya manusia secara efektif. Studi ini bertujuan untuk mengkaji integrasi Sistem Informasi Sumber Daya Manusia (SDM) dengan teknologi digital seperti Analisis SDM dan Kecerdasan Buatan (AI) dalam mengembangkan strategi sumber daya manusia yang berkelanjutan dan adaptif. Menggunakan pendekatan deskriptif kualitatif yang didukung oleh studi empiris terkini, penelitian ini menganalisis bagaimana wawasan berbasis data dan otomatisasi meningkatkan pengambilan keputusan, efisiensi operasional, dan adaptabilitas tenaga kerja. Temuan penelitian mengungkapkan bahwa integrasi SDM dengan perangkat digital meningkatkan kelincahan organisasi dengan mengoptimalkan proses manajemen talenta, mendorong keberlanjutan, dan menyelaraskan inisiatif sumber daya manusia dengan tujuan strategis. Studi ini menyimpulkan bahwa integrasi digital dalam fungsi SDM tidak hanya meningkatkan kinerja dan efisiensi, tetapi juga memperkuat ketahanan organisasi jangka panjang dalam lingkungan bisnis yang dinamis. Kata Kunci: SDM; Analisis SDM; Kecerdasan Buatan; Keberlanjutan; Kelincahan Organisasi